Antarctic representation in print media during the emergence of COVID-19 - Karen Alexander; Katrina Marx; Linda Hunt; Mengzhu Zhang (2022)
Like every other continent in the world, Antarctica has been affected by the COVID-19 pandemic, in an imagined as well as a practical sense. Antarctica is a mediated experience; that is, most of us experience the place through films, novels, music, visual arts and the media. We present an analysis of media articles from eight countries over three time periods - pre-COVID-19 outbreak (October-December 2019), shortly after the pandemic hit the headlines (March-May 2020) and when the virus was established (October-December 2020) - to discover how COVID-19 may have changed Antarctic discourse. Our study shows that representations of Antarctica have been affected by the pandemic, in some instances reinforcing existing ideas and in other cases bringing new ideas to the fore. Based on our findings, we believe that COVID-19 has begun to change representations of Antarctica, stepping us away from the prevailing Antarctic hero narrative and providing a more contemporary understanding of the Antarctic experience. We argue that this may increase our motivation to engage with Antarctic issues, with associated implications for future global stewardship of the region.